Penerapan Sanksi Tindak Pidana Asusila Oleh Pengadilan Militer I-05 Pontianak (Putusan Nomor 53-K/Pm.I-05/Ad/Ix/2017) - Anshari Anshari; Azzahra Lalili Firdaus Tupan; Nina Niken Lestari (Res Judicata, 2023)
ABSTRACKThe military has privileges in the field of law by having its own legal rules, one of which is the Military Criminal Law as a material law that is stipulated and enforced against the Indonesian National Armed Forces (TNI). At the formal level, the Military Criminal Code (KUHPM) is used. The proceedings in the Military Court are regulated in Law Number 31 of 1997 concerning Military Courts. There are also criminal cases where the perpetrator is a soldier, one of which is immoral crime which in this study is used in decision number 53-K/PM.I-05/AD/IX/2017 to critically explain the procession of first-level military court proceedings. The purpose of this study is to find out the procedures for criminalizing TNI Soldiers according to Law Number 31 of 1997 concerning Military Justice. The settlement process was carried out at the 1-05 Pontianak Military Court. In order to find out the settlement process carried out at the Pontianak 1-05 Military Court. This type of research is empirical research, using a qualitative approach, data collection techniques used by interviews, data analysis techniques with qualitative analysis. The results of this study, the State will provide sanctions to any perpetrators of violations such as criminal acts, the Military Court also has a criminal and criminal system that is guided by the Criminal Procedure Code (KUHAP) and Law Number 31 of 1997 concerning Military Courts. There are differences in the process of criminal proceedings in the General Court and the Military Court which perhaps many civil society do not know about. In decision number 53-K/PM-I.05/AD/IX/2017 it explains the process of settling an immoral crime case committed by a TNI soldier and the settlement is in accordance with the rules that apply to Law number 31 of 1997 concerning Justice Military.